Exploring the role of sigma factor gene expression on production by Corynebacterium glutamicum: sigma factor H and FMN as example - Taniguchi, Hironori; Wendisch, Volker F. (Frontiers in Microbiology, 2015)
Bacteria are known to cope with environmental changes by using alternative sigma factors binding to RNA polymerase core enzyme. Sigma factor is one of the targets to modify transcription regulation in bacteria and to influence production capacities. In this study, the effect of overexpressing each annotated sigma factor gene in C. glutamicum WT was assayed using an IPTG inducible plasmid system and different IPTG concentrations. It was revealed that growth was severely decreased when sigD or sigH were overexpressed with IPTG concentrations higher than 50 μM. Overexpression of sigH led to an obvious phenotypic change, a yellow-colored supernatant. HPLC analysis revealed that riboflavin was excreted to the medium when sigH was overexpressed and DNA microarray analysis confirmed increased expression of riboflavin biosynthesis genes. In addition, genes for enzymes related to the pentose phosphate pathway and for enzymes dependent on FMN, FAD or NADPH as cofactor were upregulated when sigH was overexpressed. To test if sigH overexpression can be exploited for production of riboflavin-derived FMN or FAD, the endogenous gene for bifunctional riboflavin kinase/FMN adenyltransferase was co-expressed with sigH from a plasmid. Balanced expression of sigH and ribF improved accumulation of riboflavin (19.8 ± 0.3 μM) and allowed for its conversion to FMN (33.1 ± 1.8 μM) in the supernatant. While a proof-of-concept was reached, conversion was not complete and titers were not high. This study revealed that inducible and gradable overexpression of sigma factor genes is an interesting approach to switch gene expression profiles and to discover untapped potential of bacteria for chemical production.